Heterogeneity of weight loss and transcriptomic signatures in pancreatic ductal adenocarcinoma - Andrea N. Riner; Kelly M. Herremans; Vignesh Vudatha; Song Han; Xufeng Qu; Jinze Liu; Nitai Mukhopadhyay; Devon C. Freudenberger; Thomas J. George; Sarah M. Judge; Andrew R. Judge; Steven J. Hughes; et al. (Wiley, 2024)
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) is highly associated with cachexia and weight loss, which is driven by the tumour's effect on the body. Data are lacking on differences in these metrics based on PDAC anatomic location. We hypothesize that the primary tumour's anatomic region influences the prevalence and severity of unintentional weight loss. Methods Treatment naïve patients with PDAC who underwent pancreatectomy at a single institution between 2012 and 2020 were identified retrospectively. Patients with pancreatic head or distal tumours were matched by sex, age, N and T stage. Serologic and anthropometric variables were obtained at the time of diagnosis. Skeletal muscle index (SMI), muscle radiation attenuation (MRA) and adiposity were measured. The primary outcome was presence of significant weight loss [>5% body weight (BW) loss in past 6 months]. Signed rank tests, Cochran Mantel Haenszel tests and Kaplan-Meier survival analysis are presented. RNA‐seq of tumours was performed to explore enriched pathways related to cachexia and weight loss. Results Pancreatic head tumours (n = 24) were associated with higher prevalence (70.8% vs. 41.7%, P = 0.081) and degree of weight loss (7.9% vs. 2.5%, P = 0.014) compared to distal tumours (n = 24). BMI (P = 0.642), SMI (P = 0.738) and MRA (P = 0.478) were similar between groups. Combining BW loss, SMI and MRA into a composite score, patients with pancreatic head cancers met more criteria associated with poor prognosis (P = 0.142). Serum albumin (3.9 vs. 4.4 g/dL, P = 0.002) was lower and bilirubin (4.5 vs. 0.4 mg/dL, P < 0.001) were higher with pancreatic head tumours. Survival differed by tumour location (P = 0.014) with numerically higher median overall survival with distal tumours (11.1 vs. 21.8 months; P = 0.066). Transcriptomic analysis revealed inactivation of appetite stimulation, weight regulation and nutrient digestion/metabolism pathways in pancreatic head tumours. Conclusions Resectable pancreatic head PDAC is associated with higher prevalence of significant weight loss and more poor prognosis features. Pancreaticobiliary obstruction and hypoalbuminemia in patients with head tumours suggests compounding effects of nutrient malabsorption and systemic inflammation on molecular drivers of cachexia, possibly contributing to shorter survival. Therefore, PDAC‐associated cachexia is a heterogenous syndrome, which may be influenced by the primary tumour location. Select patients with resectable pancreatic head tumours may benefit from nutritional rehabilitation to improve outcomes.